Belonging at the margins: nation, religion, and the Ahmadiyya Muslim Jama'at in colonial and postcolonial India, c. 1930-74 - Mehta, A (2019)
This thesis examines the history of the Ahmadiyya Muslim Jama’at in India, c. 1930-1974 through archival and printed sources in Urdu and English. It considers the multiple sites of belonging of nation, sect, and religion that the Ahmadiyya negotiated whilst remaking itself after it was devastated by Partition. The Jama’at’s strategies of self-presentation are assessed via its newspaper, al-Badr, to trace the formation of a distinct Indian Ahmadi identity in the early postcolonial period.